CONSTRAINTS ON MANTLE ANELASTICITY FROM GEODETIC OBSERVATIONS, AND IMPLICATIONS FOR THE J2 ANOMALY - Benjamin D.; Wahr J.; Ray R.D.; Egbert G.D.; Desai S.D. (My University, 2006)
We use geodetic observations of the Earth to constrain anelasticity in the Earth's mantle at periods between 12 hr and 18.6 yr. The observations include satellite laser ranging (SLR) measurements of 12 hr and 18.6 yr tides in the J2 component of the gravity field; spacebased observations of tidal variations in the Earth's rotation rate; and optical and space-based measurements of the Chandler Wobble period and damping. These geophysical signals are mostly sensitive to the lower mantle. The results suggest the dissipative process could consist of a single absorption band that extends across seismic periods out at least as far as ~20 yr. The results also require values of the anelastic parameter Q that are smaller than those required by seismic observations. We interpret this as evidence that Q in the lower mantle is frequency dependent. The frequency dependence suggested by the geodetic observations is reasonably consistent with laboratory measurements, though those measurements have only been done on rocks at upper mantle conditions. After fitting and removing the 18.6 yr tide from the SLR J2 results, we find that the 1998-2002 anomaly present in the original J2 observations is no longer a singular anomaly in the J2 residuals, but becomes one of a series of maxima in a quasi-decadal oscillation. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: EARTH ROTATION; EARTH TIDES; J2ANOMALY; MANTLE ANELASTICITY